A Short and Somewhat Personal History of Yukon Glacier Studies in the Twentieth Century - Clarke, Garry K.C. (ARCTIC, 2014)
Glaciological exploration of the Yukon for scientific purposes began in 1935, with the National Geographic Society’s Yukon Expedition led by Bradford Washburn and the Wood Yukon Expedition led by Walter Wood. However, Project “Snow Cornice,” launched by Wood in 1948, was the first expedition to have glacier science as its principal focus. Wood’s conception of the “Icefield Ranges Research Project” led the Arctic Institute of North America (AINA) to establish the Kluane Lake Research Station on the south shore of Kluane Lake in 1961. Virtually all subsequent field studies of Yukon glaciers were launched from this base. This short history attempts to document the trajectory of Yukon glacier studies from their beginnings in 1935 to the end of the 20th century. It describes glaciological programs conducted from AINA camps at the divide between Hubbard Glacier and the north arm of Kaskawulsh Glacier and at the confluence of the north and central arms of Kaskawulsh Glacier, as well as the galvanizing influence of the 1965 – 67 Steele Glacier surge and the inception and completion of the long-term Trapridge Glacier study. Excluded or minimized in this account are scientific studies that were conducted on or near glaciers, but did not have glaciers or glacier processes as their primary focus. L’exploration glaciologique du Yukon à des fins scientifiques remonte à 1935, à l’occasion de l’expédition du Yukon par la National Geographic Society dirigée par Bradford Washburn et de l’expédition Wood Yukon dirigée par Walter Wood. Cependant, le projet « Snow Cornice » mis en oeuvre par Walter Wood en 1948 a été la toute première expédition à être axée principalement sur la science des glaciers. En fait, le projet de recherche sur les chaînons des glaciers mis au point par Walter Wood a incité l’Institut arctique de l’Amérique du Nord (IAAN) à mettre sur pied la station de recherche du lac Kluane sur la rive sud du lac Kluane en 1961. Presque toutes les autres études sur le terrain relativement aux glaciers du Yukon ont eu ...